2007
DOI: 10.1145/1284621.1284627
|View full text |Cite
|
Sign up to set email alerts
|

What's wrong with online privacy policies?

Abstract: Research has shown that privacy policies tend to intensify privacy concerns rather than engender trust. One way to combat this dichotomy is to redesign their content, language, and presentation format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 10 publications
(15 reference statements)
2
84
1
18
Order By: Relevance
“…Pollach's (2005) first study, an analysis of communicative strategies in privacy statements, showed that organizations resort to both rational and emotional appeals in the construction of more credible arguments to persuade clients that their personal data would be responsibly handled. The findings of Pollach's (2007) second study suggested that privacy statements are motivated more by efforts to avoid potential lawsuits than by the obligation to uphold the principles of fair information practice.…”
Section: Privacy Statements -Defensive or Protective?mentioning
confidence: 97%
“…Pollach's (2005) first study, an analysis of communicative strategies in privacy statements, showed that organizations resort to both rational and emotional appeals in the construction of more credible arguments to persuade clients that their personal data would be responsibly handled. The findings of Pollach's (2007) second study suggested that privacy statements are motivated more by efforts to avoid potential lawsuits than by the obligation to uphold the principles of fair information practice.…”
Section: Privacy Statements -Defensive or Protective?mentioning
confidence: 97%
“…Bir anlamda, kuruluşların da bu verilerin saklanmasında ve aktarılmasında benzer kaygılara sahip olduklarını mahremiyet beyanlarında ifade etmeleri yararlı görülmektedir (Earp, 2005, 235). Pollach (2007), ABD'deki çevrimiçi politikaların kullanıcının kaygılarını azaltma yönünde tasarlanmadığını, onun yerine kuruluşları sağlık, finans ve çocukların özel yaşamlarını korumak için çıkartılmış bazı düzenlemelere karşı dava açılmaktan korumak için yapıldığını belirtmiştir. Pollach (2007) ayrıca, web sitelerinin ellerinde bulundurdukları verilerle ne gibi uygulamalar yaptıkları konusunda kullanıcılara bilgi vermelerinin güven oluşturacağını ve bu güvenle kullanıcının siteden alışveriş yapacağını, siteyi tekrar ziyaret edeceğini ve başkalarına tavsiye edeceğini de vurgulamıştır.…”
Section: Mahremiyet Beyanlarıunclassified
“…Toplanan verilerin saklanması ve paylaşılması konusunda yeterli bilgilerin verilmemesi kullanıcıyı çelişkide bırakmaktadır. Bilgiler gerçekte kullanılmamakta mıdır yoksa kasıtlı olarak belirtilmemekte midir (Pollach, 2007) gibi kullanıcıyı tedirgin edecek sorular yerine onları rahatlatacak düzeyde bilgilerin görünür yerde olması uygun bir uygulama olacaktır.…”
Section: Mahremiyet Beyanlarıunclassified
See 1 more Smart Citation
“…Additionally, information and communication technologies have dramatically improved communication, sales and information methods for companies (Lapierre and Denier, 2005;. On the problems side, some of the most commonly cited disadvantages are privacy and security issues, the difficulty of setting prices at the international level, problems of disintermediation, channel conflict intensified competition, cultural differences and the lack of socialization ( Poon, 2008;Pollach, 2007;Beheshti et al ,2006;Zittrain, 2007;Day and Bens, 2005;Paul, 1996;Rosen and Howard, 2000).…”
Section: The Business Perspectivementioning
confidence: 99%